2020
DOI: 10.1161/jaha.119.015390
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Arch and Stroke Laterality

Abstract: Background Left‐hemispheric strokes are more frequent and often have a worse outcome than their right‐hemispheric counterparts. This study aimed to evaluate whether cardioembolic stroke laterality is affected by anatomical characteristics of the aortic arch. We hypothesized that laterality varies between patients with bovine versus standard arch. Methods and Results We retrospectively identified 1598 acute cardioembolic strokes in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
0
27
1
1
Order By: Relevance
“…They observed a significantly higher prevalence of the bovine aortic arch among stroke patients (25.7%) than that among controls (17.1%) (odds ratio 1.67); stroke patients were significantly more likely to have the CILCA 2 (10.5%) than controls (5.0%) (odds ratio 2.25), while the CILCA 1 variant was similarly common in both groups, showing the higher clinical relevance of detecting the CILCA 2 variant. In addition, in a cohort of 615 stroke patients [43], left laterality of cardioembolic stroke has been shown to be significantly more frequent (51.3%) in patients with the bovine arch variant than in patients with standard arch (43.6%), demonstrating that the arch anatomy influences stroke laterality and fostering further research into the causative hemodynamic factors.…”
Section: Discussionmentioning
confidence: 93%
“…They observed a significantly higher prevalence of the bovine aortic arch among stroke patients (25.7%) than that among controls (17.1%) (odds ratio 1.67); stroke patients were significantly more likely to have the CILCA 2 (10.5%) than controls (5.0%) (odds ratio 2.25), while the CILCA 1 variant was similarly common in both groups, showing the higher clinical relevance of detecting the CILCA 2 variant. In addition, in a cohort of 615 stroke patients [43], left laterality of cardioembolic stroke has been shown to be significantly more frequent (51.3%) in patients with the bovine arch variant than in patients with standard arch (43.6%), demonstrating that the arch anatomy influences stroke laterality and fostering further research into the causative hemodynamic factors.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported the left-right propensity of cardioembolic infarcts, but no consensus has been reached so far (29)(30)(31)(32)(33)(34). Although the left hemisphere propensity of cardiogenic emboli has been reported (29,30), some researches supported the right-sided propensity of cardio-embolism, especially those associated with atrial fibrillation (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although the left hemisphere propensity of cardiogenic emboli has been reported (29,30), some researches supported the right-sided propensity of cardio-embolism, especially those associated with atrial fibrillation (31,32). A recently published work indicated that bovine aortic arch was associated with left hemisphere laterality of cardioembolic stroke compared with standard arches (33). Another work suggested that there was a trend toward right-sided lesions in patients with standard arches, but no significant difference in cardio-embolic stroke laterality of patients with bovine arches was demonstrated (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sudden obstruction of the bilateral carotid artery is rare and has seldom been reported. 1,2 In this case, the bovine arch, namely the bilateral carotid artery beginning from a brachiocephalic artery, affected simultaneously, caused serious brain damage immediately. 2…”
mentioning
confidence: 88%